Mānava Dharma-Śāstra - author, unknown (Sententiae, 2017)
The text of the selected slokas in the section "Manava-dharma-sastra", which contain the doctrine of moksha, was translated from Sanskrit by Yuri Zavgorodnim under the edition of Jolly, J. (Ed.). (1887). Mānava Dharma-Śāstra. The Code of Manu. London: Tübner.